Assessing the Impact of Micro-credit on Poverty and Vulnerability in Bangladesh - Zaman, Hassan (The World Bank, 1999)
July 1999 - While micro-credit interventions can play an important role in reducing vulnerability through a number of channels, a significant impact on poverty reduction is achieved under more restrictive conditions. These conditions revolve around whether the borrower has crossed a cumulative loan threshold and on how poor the household is to start with. Zaman examines the extent to which micro-credit reduces poverty and vulnerability through a case study of BRAC, one of the largest providers of micro-credit to the poor in Bangladesh. Household consumption data collected from 1,072 households is used to show that the largest effect on poverty arises when a moderate-poor BRAC loanee borrows more that 10,000 taka (US